Two striking head–tail galaxies in the galaxy cluster IIZW108: insights into transition to turbulence, magnetic fields, and particle re-acceleration. Issue 4 (13th October 2021) - Müller, Ancla; Pfrommer, Christoph; Ignesti, Alessandro; Moretti, Alessia; Lourenço, Ana; Paladino, Rosita; Jaffé, Yara; Gitti, Myriam; Venturi, Tiziana; Gullieuszik, Marco; Poggianti, Bianca; Vulcani, Benedetta; et al.
ABSTRACT: We present deep Jansky Very Large Array observations at 1.4 and 2.7 GHz (full polarization), as well as optical OmegaWINGS/WINGS and X-ray observations of two extended radio galaxies in the IIZW108 galaxy cluster at z = 0.04889. They show a bent tail morphology in agreement with a radio lobed galaxy falling into the cluster potential. Both galaxies are found to possess properties comparable with narrow-angle tail galaxies in the literature even though they are part of a low mass cluster. We find a spectral index steepening and an increase in fractional polarization through the galaxy jets and an ordered magnetic field component mostly aligned with the jet direction. This is likely caused by either shear due to the velocity difference of the intracluster medium and the jet fluid and/or magnetic draping of the intracluster medium across the galaxy jets. We find clear evidence that one source is showing two active galactic nuclei (AGN) outbursts from which we expect the AGN has never turned off completely. We show that pure standard electron cooling cannot explain the jet length. We demonstrate therefore that these galaxies can be used as a laboratory to study gentle re-acceleration of relativistic electrons in galaxy jets via transition from laminar to turbulent motion.